Breastfeeding Duration and Cognitive Development at 2 and 3 Years of Age in the EDEN Mother–Child Cohort - Bernard, Jonathan Y.; De Agostini, Maria; Forhan, Anne; Alfaiate, Toni; Bonet, Mercedes; Champion, Valérie; Kaminski, Monique; de Lauzon-Guillain, Blandine; Charles, Marie-Aline; Heude, Barbara (The Journal of pediatrics, 2013)
To investigate the dose–response relationship between breastfeeding duration and cognitive development in French preschool children. In the French EDEN Mother–Child Cohort Study, we evaluated language ability with the Communicative Development Inventory (CDI) in 1387 2-year-old children and overall development with the Ages and Stages Questionnaire (ASQ) in 1199 3-year-old children. Assessments were compared between breastfed and non-breastfed children and also according to breastfeeding duration in multivariable linear models, controlling for a wide range of potential confounders. We tested departure from linearity. After adjustments, ever-breastfed children scored 3.7 ± 1.8 (P = .038) points higher than never-breastfed children on the CDI and 6.2 ± 1.9 (P = .001) points higher on the ASQ. Among breastfed children, exclusive and any-breastfeeding durations were positively associated with both CDI and ASQ scores. The fine motor domain of ASQ was associated with any-breastfeeding duration, and the problem solving domain with exclusive-breastfeeding duration. We did not observe significant departures from linearity. No interactions were found between the child's sex, parental education or socioeconomic status, and breastfeeding duration. Longer breastfeeding duration was associated with better cognitive and motor development in 2- and 3-year-old children and a dose–response relationship was suggested.